Antibiotic Misuse in Pediatric Populations: Causes, Consequences, and Strategies for Mitigation - Mandal, Susmita; Shende, Deep (International Journal of Pharmaceutical Investigation, 2026)
Background The increasing risk of antibiotic resistance is a major worldwide health concern, with especially dire repercussions for children. The purpose of this study is to investigate the causes, effects, and preventative measures of paediatric antibiotic abuse. Materials and Methods A thorough investigation of the body of peer-reviewed literature, guidelines, and public health bulletins served as the foundation for this narrative review. In order to determine the main causes of antibiotic overuse and resistance in paediatric care, the study combines information from observational studies, clinical trials, and international health monitoring systems. Results The findings show that improper prescribing methods, parental pressure, ignorance, unclear diagnosis, and systemic healthcare problems are the main causes of antibiotic abuse in children. Antimicrobial Resistance (AMR) has significantly grown, adverse medication reactions have increased, and the gut microbiota has been disrupted. Evidence-based prescribing recommendations, public education campaigns, and antibiotic stewardship programs are among the interventions that have demonstrated encouraging results in lowering abuse. Conclusion The worldwide burden of antimicrobial resistance is still significantly influenced by the overuse of antibiotics in paediatric populations. Public health systems, legislators, carers, and healthcare professionals must all work together in a multidisciplinary manner to address this problem. To protect future generations' health, it is crucial to encourage ethical antibiotic use through stewardship, legislation, and education.
Keywords: Antibiotic Misuse; Pediatric Patients; Antibiotic Resistance; Antimicrobial Stewardship; Public Health.